Linezolid and Its Immunomodulatory Effect: In Vitro and In Vivo Evidence - Jin Wang; Lei Xia; Rui Wang; Yun Cai (Frontiers Media S.A., 2019)
Recent studies have explored the effects of some antibacterial agents on various aspects of the immune response to infection in addition to their bactericidal effects. As a synthetic oxazolidinone class of antibacterial agent, linezolid (LZD) exhibits activity against a broad range of Gram-positive bacteria. In the present review, we summarized the effects of LZD on the immune response and new approaches that can exploit such interactions for the treatment of bacterial infections. In vitro and pre-clinical evidence demonstrate that LZD suppresses the phagocytic ability, cytokine synthesis, and secretion of immune cells as well as the expressions of immune-related genes at the mRNA level under the stimulation of endotoxin or pathogens. Immunomodulatory effects of LZD can not only reduce the inflammatory damage induced by exaggerated or prolonged release of pro-inflammatory cytokines during infections but can also be applied to alleviate the symptoms of non-infectious inflammatory conditions. Further research is necessary to explore the molecular mechanisms involved and confirm these findings in clinical practice.